Design of novel pyrazole and benzofuran-based derivatives as potent acetylcholinesterase inhibitors for Alzheimer’s disease management - El Fadili, Mohamed; Ez-Zoubi, Amine; Aloui, Mourad; Mujwar, Somdutt; Abuelizz, Hatem A.; Elhalaoui, Menana; Amin, Adnan (Frontiers in Chemistry, 2025)
IntroductionBeing a complex neurodegenerative disease with many clinical features, Alzheimer’s disease calls for multiple-targeted drugs to treat several aspects of its progression in the human body. The present study sheds light on evaluating and designing novel pyrazole and benzofuran-based derivatives as potent acetylcholinesterase (AChE) inhibitors with improved antioxidant features to manage Alzheimer’s disease.MaterialsVarious molecular interaction fields, specifically steric, electrostatic, hydrophobic, acceptor, and donor fields of hydrogen bonds, were examined using 3D-QSAR models to predict inhibitory activity against the AChE enzyme, which was successfully validated through both external and internal assessments.Results and discussionConsequently, the CoMFA and CoMSIA/ SEHDA models led to the design of the candidate compound C27** as one of the most potent acetylcholinesterase inhibitors while building on the most active molecule (C7). Both C27** and C7 revealed their significant chemical reactivity after their optimization with B3LYP 6-31G (d, p) using the density functional theory (DFT), in addition to large similarities to the candidate drugs with desired pharmacokinetic and physicochemical features and good levels of molecular stability towards the crystal structure of human acetylcholinesterase protein (PDB ID of 4EY7).